2019
DOI: 10.3390/ijerph16122139
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Enhanced Catalytic Ozonation Oxidation of Ammonia in Aqueous Solution

Abstract: Excessive ammonia is a common pollutant in the wastewater, which can cause eutrophication, poison aquatic life, reduce water quality and even threaten human health. Ammonia in aqueous solution was converted using various systems, i.e., ozonation (O3), ultrasound (US), catalyst (SrO-Al2O3), ultrasonic ozonation (US/O3), ultrasound-enhanced SrO-Al2O3 (SrO-Al2O3/US), SrO-Al2O3 ozonation (SrO-Al2O3/O3) and ultrasound-enhanced SrO-Al2O3 ozonation (SrO-Al2O3/US/O3) under the same experimental conditions. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The use of O 3 microbubbles for NH 3 -N treatment in mine water has distinctive advantages, including the fast kinetics of the process, complete oxidation of several contaminants in mixing effluents, and no residual salinity creation in the treated water. Recently, the ultrasounds combined with ozonation and SrO-Al 2 O 3 as a catalyst showed to be promising for NH 3 -N treatment [108]. With a combination of ultrasounds at a frequency of 25 kHz vs. 270 W ultrasonic power and ozone, the NH 3 -N conversion and N 2 gas yield were 83.2% and 51.8%, respectively.…”
Section: Ozone Microbubblesmentioning
confidence: 99%
“…The use of O 3 microbubbles for NH 3 -N treatment in mine water has distinctive advantages, including the fast kinetics of the process, complete oxidation of several contaminants in mixing effluents, and no residual salinity creation in the treated water. Recently, the ultrasounds combined with ozonation and SrO-Al 2 O 3 as a catalyst showed to be promising for NH 3 -N treatment [108]. With a combination of ultrasounds at a frequency of 25 kHz vs. 270 W ultrasonic power and ozone, the NH 3 -N conversion and N 2 gas yield were 83.2% and 51.8%, respectively.…”
Section: Ozone Microbubblesmentioning
confidence: 99%
“…Thus, Chen et al [8] have shown the N 2 selectivity of 44.8% over MgO-Co 3 O 4 catalyst in the catalytic ozonation of ammonium solution. Liu et al [7] have shown the conversion of 83.2% and gaseous nitrogen selectivity of 51.8% on SrO-Al 2 O 3 catalyst in the catalytic ozonation of ammonium solution. The mechanism of catalytic ozonation of NH 4 + solution is involved with the following process.…”
Section: Modification Of Activated Dolomite With Fe 2 Omentioning
confidence: 99%
“…Liu et al demonstrated that the SrO-Al 2 O 3 composite was an effective catalyst for ultrasound-assisted ozonation of NH 4 + solution. NH 4 + conversion of 83.2% and gaseous nitrogen selectivity of 51.8% were achieved [7]. Chen et al 2018 reported the synthesis of MgO-Co 3 O 4 (molar ratio 8 : 2) and claimed that an ammonia nitrogen removal and gaseous nitrogen selectivity reached to the value of 85.2% and 44.8%, respectively [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shows that US can enhance the decomposition of O 3 and form a large number of •OH [24] . Liu et al has studied the oxidation of ammonia in different systems, and reported that less than 13 % of ammonium radical ion (NH 4 + ) is oxidized and the nitrate ion (NO 3 − ) yield is 11.2 % in the US/O 3 system, which are more than O 3 or US system [25] . Thus, the synergistic effect of US and O 3 makes up for the defects of ozone and extends the possibility of industrial application.…”
Section: Introductionmentioning
confidence: 99%